TRPC1 Deletion Causes Striatal Neuronal Cell Apoptosis and Proteomic Alterations in Mice - Wang, Dian; Yu, Haitao; Xu, Benhong; Xu, Hua; Zhang, Zaijun; Ren, Xiaohu; Yuan, Jianhui; Liu, Jianjun; Guo, Yi; Spencer, Peter S.; Yang, Xifei (Frontiers in Aging Neuroscience, 2018)
Transient receptor potential channel 1 (TRPC1) is widely expressed throughout the nervous system, while its biological role remains unclear. In this study, we showed that TRPC1 deletion caused striatal neuronal loss and significantly increased TUNEL-positive and 8-hydroxy-2'-deoxyguanosine (8-OHdG) staining in the striatum. Proteomic analysis by two-dimensional fluorescence difference gel electrophoresis (2D-DIGE) coupled with mass spectrometry (MS) revealed a total of 51 differentially expressed proteins (26 increased and 25 decreased) in the stratum of TRPC1 knockout（TRPC1-/-）mice compared to that of wild type (WT) mice. Bioinformatics analysis showed these dysregulated proteins included: oxidative stress-related proteins, synaptic proteins, endoplasmic reticulum (ER) stress-related proteins, and apoptosis-related proteins. STRING analysis showed these differential proteins have a well-established interaction network. Based on the proteomic data, we revealed by Western-blot analysis that TRPC1 deletion caused ER stress as evidenced by the dysregulation of GRP78 and PERK activation-related signaling pathway, and elevated oxidative stress as suggested by increased 8-OHdG staining, increased NDUV2 and decreased DJ-1, two oxidative stress-related proteins. In addition, we also demonstrated that TRPC1 deletion led to significantly increased apoptosis in striatum with concurrent decrease in both 14-3-3Z and dynamin-1 (D2 dopamine receptor binding), two apoptosis-related proteins. Taken together, we concluded that TRPC1 deletion might cause striatal neuronal apoptosis by disturbing multiple biological processes (i.e. ER stress, oxidative stress, and apoptosis-related signaling). These data suggest that TRPC1 may be a key player in the regulation of striatal cellular survival and death.